PRODUKSI BERAS DI INDONESIA - Hehamahua, Hayati (IQTISHODUNA, 2008)
Crop product especially rice is on of strategic and important commodities in Indonesian economic. The growing needs of rice because of the increasing population from year to year. It seems that domestic rice need projection, as principal food from year to year  will increase as explained by  USDA in the Agricultural Baseline Projection report to 20014. Import projection showed that until 2014 the domestic need for rice will increase  22-25 tons along with population increase, that is expected will reach 253 populations  in 2014 (with growth rate of 1.49% per year). This research based on secondary data that is related with research variable: land width, productivity, unhulled paddy, rice production, and rice import. The used analysis model to  test this hypothesis is Structural Equation Modeling (SEM) The results by using SEM showed that (1) land influence significantly  and positively toward rice production (2) land influence positively and positively  productivity (3) productivity influence positively and significantly toward rice production  (4) productivity influence the rice import, (5) and production influence the rice import.